The oldest metallurgy in western Europe - Ruiz-Taboada, Arturo
Recent excavations at the Neolithic site of Cerro Virtud (Almerêa, southeast Spain) have produced new information about the development of metallurgy that may change ongoing research not only in the Iberian Peninsula but also in the rest of western Europe. The discovery of metallurgy in this region in the first half of the 5th millennium BC poses serious challenges to the interpretation of how this industry developed and spread, given that the nearest European region with similar evidence is the Balkans. This study presents the archaeological context of the discovery and the various analytical techniques